Methadone-Induced Delayed Posthypoxic Encephalopathy: Clinical, Radiological, and Pathological Findings - Manoj Mittal; Yunxia Wang; Alan Reeves; Kathy Newell (Case Reports in Medicine)
Objective. To describe the clinical, radiological and pathological findings in a patient with methadone-induced delayed posthypoxic encephalopathy (DPHE). Case Report. A Thirty-eight-year-old man was found unconscious for an unknown duration after methadone and diazepam ingestion. His initial vitals were temperature 104 degree Fahrenheit, heart rate 148/minute, respiratory rate 50/minute, and blood pressure 107/72 mmhg. He developed renal failure, rhabdomyolysis, and elevated liver enzymes which resolved completely in 6 days. After 2 weeks from discharge he had progressive deterioration of his cognitive, behavioral and neurological function. Brain MRI showed diffuse abnormal T2 signal in the corona radiata, centrum semiovale, and subcortical white matter throughout all lobes. Extensive work up was negative for any metabolic, infectious or autoimmune disorder. Brain biopsy showed significant axonal injury in the white matter. He was treated successfully with combination of steroids and antioxidants. Follow up at 2 year showed no residual deficits. Conclusion. Our observation suggests that patients on methadone therapy should be monitored for any neurological or psychiatric symptoms, and in suspected cases MRI brain may help to make the diagnosis of DPHE. A trial of steroids and antioxidants may be considered in these patients.